Izolovaná a kombinovaná oklúzia cilioretinálnej artérie a centrálnej vény sietnice - Streicher, T; Spirková, J (Ceska a slovenska oftalmologie, 2001)
Cilioretinal artery occlusion is rare pathological condition because of infrequent occurrence of the cilioretinal artery in the human retina. It presents as an isolated entity, or as a combined cilioretinal artery--central retinal vascular, mostly venous occlusion. Authors present the course, angiographic features, prognosis, risk factors and final outcome of the isolated cilioretinal artery occlusion and combined cilioretinal artery--central retinal vein occlusion. Occlusion of the cilioretinal artery is believed to result from obstruction of the central retinal vein, as a primary process, in the case of combined cilioretinal artery--central retinal vein occlusion.
Keywords: Humans; fluoresceinová angiografie; okluze retinální arterie; lidé středního věku; dospělí; okluze retinální žíly; Arterial Occlusive Diseases; lidé; arteriální okluzní nemoci; Retinal Vein Occlusion; Fluorescein Angiography; ciliární arterie; Adult; arteria centralis retinae; Male; Middle Aged; prognóza; Ciliary Arteries; Retinal Artery; vena centralis retinae; Retinal Artery Occlusion; Retinal Vein; mužské pohlaví; Prognosis